Film Techniques in the Poetry by Alexey Salnikov - Podlubnova, Yu. S. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2016)
The article studies the impact of cinematic techniques as part of the text-generating strategies of modern poetry. Referring to the works by Ural poet Alexei Salnikov (born in 1978), who combines the artistic potential of the word with visual techniques, the author describes the poet’s need to use long and slow motion frames in his texts. Long and slow motion frames combine the potentials of the cinema and photography. In the Ural author’s poetry, long and slow motion frames are characterized by the loss of the semantic oppositions in pairs of notions “materiality / factuality”, “staging / accident”, “duration / instantaneity”. The combination and alternation of such frames in a poetic text reflect the specific character of artistic vision where one of the features is the poet’s transferring of his visual function to the subject included in the self-valuable process of experiencing reality. A. Salnikov’s visual series are a way to express some existential experience through the visual where vision is only the starting point to model the situation of experience, and this process of experience has some temporal characteristics. This is the reason why the long and slow motion frames and their duration perform a special role in the poetry by A. Salnikov.